Pengaruh Aplikasi Proteus Terhadap Kemampuan Belajar Mandiri Pada Siswa Teknik Elektronika: Sebuah Kajian Literatur - Putra, Riko; Rusjiono, Rusjiono; Susarno, Lamijan Hadi; Arianto, Fajar (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
Independent learning ability is a person's ability to learn and develop knowledge, skills and understanding independently. Independent learning abilities involve cognitive abilities, strategies, and attitudes that enable a person to take initiative in their own learning process. The ability to learn independently also has an impact on the 21st century skills that students must have, these skills include creative thinking, critical thinking and problem solving, communicating and collaborating. On the other hand, in class it is often found that Electronics Engineering students are still weak in their independent learning abilities. The role of the teacher is still dominant and is the only source of learning for students in solving problems. The main cause is thought to be that learning media is less effective in increasing independent learning so that students are too dependent on teachers. The aim of this research is to analyze the effect of the Proteus application on the independent learning abilities of Electronics Engineering students. The research method used is a narrative literature review. A total of 20 articles from international journals were used as research samples. Research findings show that the Proteus application has an influence in improving the independent learning abilities of Industrial Electronics Engineering students. This is supported by the data contained in each research sample. Implementing the Proteus application can also be an alternative in improving students' 21st century abilities. However, this research only examines one type of media. Recommendations for further research can be carried out by comparing the effectiveness of the Proteus application with other applications used in learning Industrial Electronics Engineering.